BUSINESS ETHICS AND THE INFLUENCE OF VOICE COMMERCE (SMART SPEAKER)-BASED DIGITAL MARKETING ON PURCHASING DECISIONS - Ilham Akbar; Abdi Wijaya (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
Digital  transformation  has  introduced  voice  commerce  as  an  innovation  in  artificial  intelligence–based  marketing  strategies,  enabling  consumers  to  interact  through  voice  commands.  This  study  aims  to  examine  the  influence  of  business  ethics  and  voice  commerce–based  digital  marketing  on  purchase  decisions,  with  consumer  trust  as  a  mediating  variable.  The  research  employed  an  explanatory  quantitative  approach  with  250  respondents  who  use  smart  speakers  in  Indonesia.  Data  were  analyzed  using  Partial  Least  Squares–Structural  Equation  Modeling  (PLS-SEM)  to  evaluate  the  interrelationships  among  variables  and  the  strength  of  mediation.  The  findings  reveal  that  business  ethics  significantly  and  positively  influence  consumer  trust,  which  subsequently  increases  purchase  decisions.  Moreover,  voice  commerce  enhances  the  emotional  connection  between  users  and  brands  through  natural  and  personalized  interactions,  although  privacy  and  data  security  remain  key  concerns.  Consumer  trust  acts  as  a  crucial  mediator  linking  ethical  business  practices  to  purchase  decisions.  The  results  confirm  that  the  integration  of  moral  values  and  digital  technology  shapes  ethical  and  sustainable  consumer  behavior.  This  study  concludes  that  the  success  of  digital  marketing  in  the  voice  commerce  era  depends  on  how  well  companies  uphold  fairness,  transparency,  and  social  responsibility  principles  in  the  use  of  voice  technology.  The  theoretical  contribution  lies  in  the  development  of  the  Ethical  Voice  Commerce  Framework,  while  the  practical  implication  emphasizes  the  importance  of  implementing  digital  ethics  governance  to  enhance  consumer  trust  and  loyalty.